ETV6-RUNX1 Rearrangement in Tunisian Pediatric B-Lineage Acute Lymphoblastic Leukemia - Abir Gmidène; Hatem Elghezal; Hlima Sennana; Yosra Ben Youssef; Balkiss Meddeb; Moez Elloumi; Abderrahim Khlif; Ali Saad (Advances in Hematology)
In this study, Forty-one out of fifty-seven Tunisian children with B-lineage acute lymphoblastic leukemia (B-ALL), and without cytogenetically detectable recurrent abnormalities at the time of the diagnosis, were evaluated by fluorescence in situ hybridization (FISH) for the t(12;21). This translocation leads ETV6-RUNX1 (previously TEL-AML1) fusion gene. 16 patients (28%) had ETV6-RUNX1 rearrangement. In addition to this rearrangement, two cases showed a loss of the normal ETV6 allele, and three others showed an extra signal of the RUNX1 gene. Seven patients without ETV6-RUNX1 rearrangement showed extra signals of the RUNX1 gene. One out of the 7 patients was also associated with a t(3;12) identified by FISH. This is the first Tunisian study in which we report the incidence of t(12;21) among childhood B-lineage ALL and in which we have found multiple copies of RUNX1. Finally, our findings confirm that additional or secondary genetic changes are commonly encountered in pediatric B-lineage ALL with ETV6-RUNX1 gene fusion which is envisaged to play a pivotal role in disease progression.